Innovative engineering training in a competitive educational environment - N. I. Naumkin; N. N. Shekshaeva; E. V. Zabrodina (Образование и наука)
Introduction. The level of mastery of innovative engineering has always determined the qualifications of engineering personnel, who ensure the technological progress of society and the modern technological structure of its economy. In this regard, the problem of increasing the efficiency of preparation for such activities is relevant. To solve it, an appropriate educational environment is created. This educational environment involves a teaching, developmental, upbringing, control-diagnostic and reflective means, which allows various pedagogical conditions, including innovative activities, to be simulated. The most effective of them are competitive environments, due to the increased motivation of their subjects for learning, formed when the natural quality of a person, i.e. competitiveness, is developed in them. However, these environments do not fully disclose the mechanism of formation of motivation and its structure. This raises the dilemma of creating a new competitive educational environment based on the use of competitiveness.The aim of the present research is to increase the efficiency of university students' training for innovative engineering activities due to high motivation to master it through the use of competitiveness.Methodology and research methods. In the current research, the authors were guided by the concept of multi-level and multi-stage preparation of university students for innovative engineering activities. For its implementation, a methodological system was used, including: 1) approaches to learning (integrated, interdisciplinary, systemic, substrate and structured), aimed at creating a competitive educational environment with its specific hierarchy, structure and substrates; 2) methods (competitions - to provide increased motivation; hypothetical-deductive method - to put forward a hypothesis; morphology - to analyse and choose methods; pedagogy of cooperation - to create a comfortable environment); 3) principles (competitiveness, unity of fundamental and professional orientation, interdisciplinarity and interdisciplinarity, etc.).Results and scientific novelty. In the course of the research, a competitive educational environment was created as a system of interacting subjects and objects of educational activity, which has a multicomponent structure. During its developmental process, special attention was paid to the design of models of organisational forms of its implementation, common to which is the high personal motivation of the participants due to the presence of competition, competitive spirit and rivalry. One of them is the All-Russian Scientific Student Festival and related events, annually organised by the authors. The features of increased motivation formation to master innovative activities in these conditions among students, taking into account their psychological and behavioural characteristics, were considered as well. Its structure was revealed as a set of motives, which encourage the individual to be involved in a particular activity. The motives are determined not only by the ability to realise the student's personal quality of competitiveness, but also by other motives caused by emotions they experience at the stages of the competitive substrate of the festival (preparation - performance - analysis). This constitutes the scientific novelty of the research conducted by the authors.Practical significance. The methodological system of research is concretised. The methods have been created for organising and holding the festival, teaching innovative engineering activities in a competitive educational environment based on the involvement of students in all stages of innovative activities and increased motivation to master it. Methodological support for the functioning of the educational environment has been developed.